2015
DOI: 10.1371/journal.pone.0139031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Previous Land-Use on Plant Species Composition and Diversity in Mediterranean Forests

Abstract: At some point in their history, most forests in the Mediterranean Basin have been subjected to intensive management or converted to agriculture land. Knowing how forest plant communities recovered after the abandonment of forest-management or agricultural practices (including livestock grazing) provides a basis for investigating how previous land management have affected plant species diversity and composition in forest ecosystems. Our study investigated the consequences of historical “land management” practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…In some studies, in situ PLU remnants were also recorded to confirm the accuracy of the historical map used (e.g. Peterken and Game, 1984), but thanks to the recent availability of large scale historical maps (Kaim et al, 2016), more and more studies are carried out without field survey (Kouba et al, 2015;Bergès et al, 2016). Here we underline the limitations of using historical maps, especially in our Mediterranean context.…”
Section: Is the Etat-major Map Relevant In A Mediterranean Context?mentioning
confidence: 68%
See 1 more Smart Citation
“…In some studies, in situ PLU remnants were also recorded to confirm the accuracy of the historical map used (e.g. Peterken and Game, 1984), but thanks to the recent availability of large scale historical maps (Kaim et al, 2016), more and more studies are carried out without field survey (Kouba et al, 2015;Bergès et al, 2016). Here we underline the limitations of using historical maps, especially in our Mediterranean context.…”
Section: Is the Etat-major Map Relevant In A Mediterranean Context?mentioning
confidence: 68%
“…Land use legacies on current forest soils, species richness and composition have been much less explored in Mediterranean forests compared to temperate forests (Amici et al, 2013;Kouba et al, 2015;Basnou et al, 2016). Basnou et al (2016) found that forest continuity had a weak effect on woody species, while Kouba et al (2015) highlighted a loss in late-successional species in Mediterranean forests due to intensive and widespread previous agricultural use in this region. Amici et al (2013) showed that light-demanding species richness decreased with increasing successional age of forest, despite the open forest canopy measured in forests at all successional ages.…”
Section: Introductionmentioning
confidence: 99%
“…Within each site, three 200-m linear transects (30 transects in total) were carried out. Plant abundance and richness within each transect were estimated using the Point-Intercept Method (Goodall 1952), which consists of recording, at every 20-cm intervals, the identity of all individuals that are in contact with a vertical nail (Kouba et al 2015). The abundance of each species in each transect was estimated from the number of individuals recorded along the same transect.…”
Section: Sampling Methods Of Vegetationmentioning
confidence: 99%
“…Similarly, Paillet et al (2010) recorded the decrease of the evenness of early-successional shadeintolerant species for the benefit of intermediate-successional species due to the shadier conditions prevailing in the later stages of the succession. In addition, this decline of evenness in annuals species can be explained by the greater dominance of perennial species and shrubs, which are superior competitors for resources (Kouba et al 2015).…”
Section: Soil-based Functions Along Abandonment Gradientmentioning
confidence: 99%